PENERAPAN MEDIA GAMBAR DALAM MENINGKATKAN KEMAMPUAN MENULIS BERITA - Diah Nurwulandini; Suleman Suleman (Program Studi Pendidikan Guru Sekolah Dasar Universitas Muhammdiyah Gorontalo, 2025)
This research aims to improve students’ ability to write news sentences through the use of picture media among fifth-grade students at SDN 11 Limboto, Gorontalo Regency. This research is a classroom action research involving 25 fifth-grade students of SDN 11 Limboto as the subjects. The data analysis techniques included data on teacher activities, student activities, and students’ speaking abilities. In the initial observation, only 7 students, or 28%, achieved mastery based on the minimum competency criterion (KKM) of 75. The results of the study in Cycle I showed that 17 students, or 68%, achieved mastery. In Cycle II, the number increased to 23 students, or 92%, indicating an improvement of 24%. Thus, it can be concluded that the use of picture media can enhance students’ writing skills in Indonesian language learning among fifth-grade students at SDN 11 Limboto.